Analisis Kandungan Merkuri dan Timbal pada Sediaan Krim Malam Menggunakan Spektrofotometri Serapan Atom - RK Sanjaya (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Mercury (Hg) and lead (Pb) are heavy metals that are toxic and carcinogenic, but nowadays many skin care cosmetics use Hg as a bleach and preservative. Considering the potential danger, it is necessary to analyze the mercury and lead content which is accurate and has a low detection limit. In this study, analysis of Hg and Pb content in night cream using atomic absorption spectrometer was carried out. As samples, two-night creams which are widely circulated in Kediri were selected. Sample preparation was carried out through destruction using HNO3 and HCl in a ratio of 1:3, then the concentrations of Hg and Pb were determined using a calibration curve. The performance of the methods used included accuracy of 98 and 99%, RSD of 0.16 and 0.14% and detection limits of 0.073 and 0.022 μg/mL for Hg and Pb, respectively. The levels of Hg in both samples were 10.16 mg/L and 504.89 mg/L. Meanwhile, the Pb level was below the detection limit of the method so it was not detected. Due to high content of Hg (>1 mg/L) the two cosmetic samples are not safe for use by consumers.